Enhancing Children's Gross Motor Skills Through the Single Leg Balance Sandbag Game - Rusmayadi, Rusmayadi; Kurnia, Rika; Aziza, Sazkiyah (Program Studi Magister Pendidikan Anak Usia Dini, 2024)
Development motor rough child considered important, because If development motor rough child develop optimally then in a way No direct will influence behavior child daily. If growth physical and motoric child develop optimally, then activity motion child will become more ripe and more good . This research aims to to find out whether there is any influence game single leg balance sand bag on the gross motor skills of early childhood children . The research approach used is a quantitative approach with a Quasi Experimental research type which includes an experimental group and a control group. Data collection techniques include tests, observations, and documentation. Data analysis techniques used in study This is a descriptive data analysis and non-parametric statistical analysis with a population of 20. From the results of the non-parametric data analysis, it can be proven that the game single leg balance sand bag can has a significant influence on gross motor skills in children. Single leg balance sand bag game can affect gross motor skills in early childhood. This game can have a positive influence on children's gross motor skills. It is expected that with the Single leg balance sand bag game, children will be more enthusiastic in learning activities, can socialize well and develop more in children's gross motor skills